Distribuição longitudinal de sementes de milho e soja em função do tubo condutor, mecanismo dosador e densidade de semeadura - Carpes, Dauto Pivetta (2014)
The competitiveness of the agricultural sector allows producers to seek technology that operate, in a manner, precisely as possible. Some crops have great sensitivity to population change and also the arrangement of the spacing between seeds in the row. Thus, the performance of the seed distribution mechanisms should provide the widest possible range of acceptable spacing, which will contribute that the crop(s) will reach the satisfactory levels of productivity. The purpose of this study was to evaluate the effect of the type of conductor pipe, equipped with a horizontal honeycomb disc and a pneumatic, varying the sowing rate, and the peripheral speed of the seed feeder discs. The experiment was conducted in a laboratory complying with ISO, ABNT, and Project ABNT standards. Treatments consist of a combination of two feeders with six conductor pipes, changing the peripheral speed of the feeder disk to densities obtained: 250,000; 300,000; 350,000; and 400,000 seeds h-1 for soybean, and 60,000; 70,000; 80,000; and 90,000 seeds ha-1 for corn, arranged in a factorial design with four replications for each crop. The conductor tubes were selected based on shape and diameter input and output of seeds, length and size, and evaluating the influence of the way the seeds are released (natural or forced). By increasing the density of seeds ha-1, it decreased the percentage of acceptable spacing, this effect was more accentuated for soybean seeds and when conductor tubes were used with small diameter pipes and straight profile. For corn seed conductor tubes, it also caused reduction in the longitudinal distribution of regularity, but with lower intensity when compared to soybean seeds.